Pengaturan Sanksi Pidana Undang-Undang Cipta Kerja D Alam Upaya Pemulihan Lingkungan Pasca Tambang - Muhammad Arya Ramadani; Aulia Vivi Yulianingrum (CV Putra Publisher, 2024)
The aim of this research is to determine the criminal provisions relating to environmental permits according to the Job Creation Law (UUCK) and the Environmental Protection and Management Law (UUPPLH). Apart from that, know the form of simplifying business licensing procedures according to UUCK. And to find out the model of criminal provisions that are suitable for environmental restoration. The research method that will be used in this research is normative juridical, namely (Normative Legal Research Method), namely by applying this research through library materials or only secondary data. The research results show that damage, especially to the environment, which is carried out by perpetrators, especially in a mining business, cannot be avoided. Finally, the forest, which has been running well, and the demolition of this land has reached hundreds of hectares, causing it to no longer function as usual, causing drought and barrenness due to the loss of soil fertility due to demolition, which makes it one of the procedures that must be used in in the mining business. Therefore, the perpetrators of environmental pollution and/or destruction who have committed criminal acts, must be held responsible, because they have deliberately committed them, without any excuse as stated in the provisions of the formulation, namely criminal acts against the environment. As a result, the provisions on criminal sanctions are used as one of the last means (ultimum remidium) in an effort to enforce the obligation to carry out reclamation and post-mining activities.